PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN PT. UNILEVER INDONESIA DI KOTA PEKANBARU - minly tandi wati; alvi furwanti alwie; samsir samsir (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: The fast development of business world causes various types of consumer neededitems can be easily obtained so the company need to improve their performance. One thingthat can improve customer satisfaction and create loyalty is Corporate Social Responsibility(CSR).The purpose of this study is to determine the effect of Carroll Pyramid CSR (economic,legal, ethical, philanthropic) towards customer satisfaction and loyalty. The population in thisstudy were all PT. Unilever Indonesia customer in Pekanbaru with sample of 240 respondents.Data was collected through questionnaires and data analysis method is Structural EquationModeling (SEM) using software AMOS 21. Based on the research results, economic andethical CSR has positive and significant impact on consumer satisfaction, while legal andphilanthropic has positive but not significant impact on customer satisfaction. Economic,legal, ethical, philanthropic CSR and satisfaction has positive and significant impact oncustomer loyalty. Therefore, this study recommends PT. Unilever Indonesia to ensure andenhance its CSR activities. Especially for legal and philanthropic CSR, PT. UnileverIndonesia need to communicate the importance of legal CSR in long term for the environmentand the importance of philanthropic CSR to improve social conditions of the society. CSRactivity is very beneficial to society, therefore further CSR activity is expected to enlarged forall regions in Indonesia.Keywords: Corporate Social Responsibility (CSR), Customer Satisfaction, and CustomerLoyalty.